2003
DOI: 10.1002/ange.200351405
|View full text |Cite
|
Sign up to set email alerts
|

Regio‐ and Enantioselective Synthesis of Allylic Fluorides by Electrophilic Fluorodesilylation of Allyl Silanes

Abstract: Enantiomerenreine N‐Fluor‐Cinchona‐Alkaloide katalysieren die elektrophile Fluordesilylierung von Allylsilanen. Dieses neue Konzept ermöglicht die regio‐ und enantioselektive Synthese von Allylfluoriden (siehe Schema). Bei hervorragenden Ausbeuten konnten Enantiomerenüberschüsse bis zu 96 % ee erzielt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…The conformational differences appear even more marked for the minor isomer (À)-8 b. This was studied in both CDCl 3 and C 6 D 6 , the latter removing the troublesome coincidence of H 5 anti did share a large value of 9.1 Hz. In addition,…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The conformational differences appear even more marked for the minor isomer (À)-8 b. This was studied in both CDCl 3 and C 6 D 6 , the latter removing the troublesome coincidence of H 5 anti did share a large value of 9.1 Hz. In addition,…”
Section: Introductionmentioning
confidence: 97%
“…Noteworthy exceptions are the fluorinated analogues of shikimic acids, which are of relevance as potential antifungal, antibacterial and antiparasitic agents. [4] On the basis of relevant precedent from our laboratory, [5] we reasoned that compounds of general structure I (Scheme 1) could be prepared by diastereoselective electrophilic fluorodesilylation of the corresponding enantioenriched allylsilanes. A known catalytic asymmetric desymmetrization process will enable the construction of the starting enantioenriched dihydroxylated cyclic allylsilanes.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that enantioenriched allylic fluorides can be prepared using a reagent-controlled enantioselective fluorodesilylation of prochiral allylsilanes, affording fluorinated carbocycles with a single stereogenic center. [5] In pursuit of a general strategy for the enantioselective synthesis of fluorinated sixmembered carbocycles featuring multiple stereocenters, one of which is fluorinated, it is tempting to resort to the DielsAlder reaction using a monofluorinated diene [6] or dienophile (Scheme 1). [7] However, an asymmetric catalytic approach has yet to be developed, not least because of reactivity and selectivity issues, and the need to prepare the fluorinated reactants with perfect control of their E/Z geometry.…”
mentioning
confidence: 99%
“…As a compromise of both yield and enantioselectivity, a catalyst loading of 15 mol % was selected for the ensuing study. Lowering the reaction temperature to 0 8C brought no improvement in enantioselectivity, but led to a decrease in the yield and a prolonged reaction time ( [8][9][10][11]. Although higher ee values were obtained in Et 2 O or methyl tert-butyl ether (MTBE), the yields were markedly diminished probably due to the poor solubility of NFSI in these two solvents (Table 2, entries 12 and 15).…”
mentioning
confidence: 91%
“…[8,9] Our group has developed a onepot tandem reaction for the synthesis of fluorinated flavanones, from b-ketoesters and aldehydes, with excellent diastereoselectivities.…”
mentioning
confidence: 99%